Perancangan Strategi Usaha dan Penerapan Etika Bisnis Untuk Meningkatkan Penjualan di Bakso Mas Bro Palembang - Muhammad Distian Andi Hermawan; Debi Septiani; Ermalia; Septyana; Musdalipah; Regina Pramita (Jurnal Ilmiah Manajemen Ekonomi Dan Akuntansi (JIMEA), 2023)
The purpose of this study is to see how the business process is carried out and how the development of the business is carried out and how the process of applying ethics in doing business. The research method carried out in this study is using a descriptive qualitative approach where descriptive qualitative research is only looking at and describing the results of case studies in the field, the case study used in this study is Mas Bro Palembang meatballs. The results of this study show that the business run by Mr. Dirman as the owner of the Bakso Mas Bro Palembang MSME, that he has applied ethics in doing business and has also adjusted to circumstances and conditions such as consumer and customer demand and also the Pak Dirman meatball business has applied ethics in doing business and also has a strategy in selling.